Effect of different preparation techniques of red dragon fruit (Hylocereus polyrhizus) extracts on normal human fibroblast viability - Novi Febrianti; Triana Hertiani; Sukarti Moeljopawiro; Sofia Mubarika Haryana (Universitas Ahmad Dahlan, 2019)
Red dragon fruit is one of the popular fruits that have been widely used both for consumption and food coloring. The red dragon fruit peel and flesh contain various antioxidant compounds that can be used as pharmaceutics and nutraceuticals. The objective of this study was to determine the effect of various extract preparations of the peel and the flesh of red dragon fruit on the viability of normal human fibroblasts. Seven conditions of peel and flesh extracts were prepared as follows, i.e. dried peel ethanolic extract, fresh blended peel ethanolic extract, dried flesh, fresh blended flesh ethanolic extract, blended fresh flesh, filtrate of pressed flesh, and pomace of pressed flesh. Each sample preparation was tested for its effect on the viability of normal human fibroblasts using MTT assay. Results showed that dried peel ethanolic extract reduce cell viability. Red dragon fruit flesh extracts caused no significant effect on the fibroblast viability. In conclusion, the fruit flesh extracts are relatively safer to normal cells than the peel extracts. IC50 value of the ethanolic extract of dried peel was 55.38±3.85 µg/mL, while the IC50 value of various types of flesh extract were more than 500 µg/mL.